Improving MSME Marketing Performance Through Digital Business Literacy - Mesakh, Januardi; Saragih, Rintan; Situmorang, Duma Rahel; Panjaitan, Rike Yolanda; Silalahi, Mulatua P.; Sipayung, Tri Darma; Sibarani, Apriani Magdalena; Sipayung, Saur Melianna; Simanjuntak, Rimky Mandala Putra; Nainggolan, Rahel Junita (Jurnal Pengabdian Masyarakat Bestari, 2024)
Currently, digital business development is increasingly rapid. Digitalization plays a very important role for companies, especially MSMEs, to increase product sales. Consumers can easily access products through the service provider's digital services. Therefore, the aim of this community service is to provide an understanding of digital business skills to MSME stakeholders in Medan, North Sumatra, by involving 15 MSME actors. This is in line with one of the government programs to help MSMEs optimize the use of information and communication technology in their business operations, known as the MSME go digital program. This activity is expected to help MSME players better understand and improve their digital business capabilities and improve business performance.